2019
DOI: 10.1111/tbed.13262
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flavivirus co‐circulation in serological diagnostics and surveillance: A model of study using West Nile, Usutu and Bagaza viruses

Abstract: This study aims at assessing the serological cross‐reactions existing between three mosquito‐borne flaviviruses with avian reservoirs co‐circulating in Europe: West Nile (WNV), Usutu (USUV) and Bagaza (BAGV). The study is useful for a better interpretation of serological results in diagnostics and surveillance. Serum samples obtained from a natural host, the red‐legged partridge (Alectoris rufa), experimentally infected with WNV, USUV or BAGV were analysed using two commercially available WNV competition ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…From 2018 onwards, 64% of the Eurasian magpies tested in the study area were positive for flaviviruses (i.e., cELISA positive) and 15% were confirmed as positives for WNV by SNT. These results suggest that the cELISA used allowed the detection of flaviviruses different to WNV that were circulating in the studied area, which is in agreement with a recent study that has demonstrated the presence of cross-reactions between WNV and other flaviviruses such as BAGV or Usutu virus (USUV) when the IDvet kit was used [25]. In fact, antibodies against BAGV were detected by SNT in a magpie sampled in June 2018, which is the first time in this bird species.…”
Section: Discussionsupporting
confidence: 90%
“…From 2018 onwards, 64% of the Eurasian magpies tested in the study area were positive for flaviviruses (i.e., cELISA positive) and 15% were confirmed as positives for WNV by SNT. These results suggest that the cELISA used allowed the detection of flaviviruses different to WNV that were circulating in the studied area, which is in agreement with a recent study that has demonstrated the presence of cross-reactions between WNV and other flaviviruses such as BAGV or Usutu virus (USUV) when the IDvet kit was used [25]. In fact, antibodies against BAGV were detected by SNT in a magpie sampled in June 2018, which is the first time in this bird species.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the envelope protein of USUV shares some structural features with the WNV envelope [33,34], and antibody cross-reactivity has been observed [35]. Thus, serological tests, such as ELISAs, cannot always distinguish USUV from WNV, which has led to the hypothesis that USUV circulation may be underestimated [36]. Other assays, such as protein microarray based on NS1 [37] or quantitative multiplex real-time RT-PCR [38], have been developed in recent years.…”
Section: Transmission Dynamicsmentioning
confidence: 99%
“…Antibodies against flaviviruses were detected using a commercial competitive enzyme-linked immunosorbent assay (cELISA; ID Screen ® West Nile Competition, ID Vet, Montpellier, France) based on purified whole WNV antigen for the detection of antibodies directed against the envelope E protein common to all flaviviruses. Although this ELISA test is designed for WNV detection, the high cross-reactivity observed makes this method suitable for the detection of a broad range of flavivirus antibodies [38,39]. The test was performed according to the manufacturer's instructions and interpreted following their recommendations: samples with a sample-to-negative control (S/N) ratio ≤ 40%, [40-50%] and > 50% were considered positive, doubtful and negative, respectively.…”
Section: Laboratory Analysismentioning
confidence: 99%